Financial burden on the parents of children infected with extensively drug resistant Salmonella infection (Journal of Fatima Jinnah Medical University, 2022)
Background: Typhoid illness is a significant cause of morbidity in Pakistan. This study aimed to determine the financial burden on parents of children infected with extensively drug-resistant (XDR) salmonella infection.Patients and methods: This observational study included 159 patients aged 6 months to 13 years admitted through OPD/ER of Karachi Adventist Hospital with the diagnosis of enteric fever and intravenous antibiotics started as per local antibiogram. To remove recall bias antibiotic cost before hospitalization was not included. All those patients who were culture positive for XDR salmonella, either continued or shifted to newer antibiotics as per susceptibility pattern were included. Depending upon the type and duration of antibiotic therapy cost was calculated in Pakistani rupee (1 USD = ~225 PKR).Results: Total 60.4% of patients aged less than 7.5 years; 62.3% were male, 41.5% from urban areas, 15.1% had graduated mothers, 27% had graduated fathers, 5.7% uses boiled water, and 1.9% typhoid vaccination. In 54.1% of patients antibiotic cost reached >40k PKR. Patients with urban dwelling were 0.29 times less likely for higher cost, increase in duration of fever (>7 days) at admission increased the cost 5.73 times, XDR samples found 13.5 time more likely for higher cost, and TLC between 4000 – 11000/mm3 gave negative association with higher cost.Conclusion: The burden of XDR salmonella infection is heavy and is related to urban residence, duration of fever at admission, and length of hospital stay.
Keywords: Financial burden; Children; XDR; Salmonella; Antibiotic